THE TRIUMPH OF THE STATE: SINGAPORE'S DOCKWORKERS AND THE LIMITS OF GLOBAL HISTORY, c. 1920–1965*. (3rd April 2017) - CURLESS, GARETH
Abstract: Labour history has been revitalized by the global turn. It has encouraged historians to look beyond national frameworks to explore issues relating to mobility and inter-territorial connection. This article, while accepting the benefits of a global approach, argues that historians should not lose sight of the factors that constrain mobility or lead to the collapse of cross-border exchanges. Singapore's dockworkers were at the forefront of the island's anti-colonial campaigns of the 1940s and 1950s. Inspired by anti-colonial movements elsewhere in the world, dockworkers drew on international discourses relating to self-determination to place their local struggles in a global context. This activism, however, coincided with the emergence of countervailing forces, including the universalization of the nation-state and the rise of state-led developmentalism. In this context, dockworkers' internationalism came to be regarded as a threat to state sovereignty and development. As a result, once Singapore achieved independence the ruling People's Action Party encouraged dockworkers to abandon their globalized outlook in the name of modernization and nation building. Global history, then, should be as much about the rise of the national as the transnational, and the loss of connection as the forging of inter-territorial networks.